Significance of Agro-Textiles and Future Prospects in Bangladesh - Chowdhury, Md. Jonayet; Nasrin, Shamima; Faruque, Md. Abdullah Al (European Scientific Journal, ESJ, 2017)
Agro-textile is a crucial and emerging sector among all the twelve sectors of technical textiles. It covers all the textile products from horticulture application to fishing and animal husbandry application. However, the significance of agro-textiles can be stated substantial all over the world. Also in Bangladesh, some application of agro-textiles products have shown great extent of outcomes and it has positive impacts on growth and production of various crops, vegetables. The main purpose of this research is to deliver an overview and importance of agro-textiles and to indicate the prospect of agro-textiles in future of Bangladesh. For this research some market analysis has been done, which implies some indication about the rise in utilization and also in local production of agro-tech. An alternate intention of this study to make the industrialists, the businessmen and the entrepreneurs comprehend about this sector and to encourage them in investment.